Opinion about seasonal influenza vaccination among the general population 3 years after the A(H1N1)pdm2009 influenza pandemic. Issue 48 (27th November 2015) - Boiron, Karine; Sarazin, Marianne; Debin, Marion; Raude, Jocelyn; Rossignol, Louise; Guerrisi, Caroline; Odinkemelu, Didi; Hanslik, Thomas; Colizza, Vittoria; Blanchon, Thierry
Highlights: In France, 39% reported a positive opinion regarding seasonal flu vaccination. 39% and 22% reported a neutral and a negative opinion. Healthy young adults were more inclined to have neutral or negative opinions. As well as those preferring homeopathic treatments. And those who did not work in contact with elderly or sick individuals. Abstract: Objective: To assess the opinions of the French general population about seasonal influenza vaccination three years after the A(H1N1)pdm 09 pandemic and identify factors associated with a neutral or negative opinion about this vaccination. Study design: The study was conducted using data collected from 5374 participants during the 2012/2013 season of the GrippeNet.fr study. The opinion about seasonal influenza vaccination was studied on three levels ("positive", "negative" or "neutral"). The link between the participant's characteristics and their opinion regarding the seasonal influenza vaccination were studied using a multinomial logistic regression with categorical variables. The "positive" opinion was used as the reference for identifying individuals being at risk of having a "neutral" or a "negative" opinion. Results: Among the participants, 39% reported having a positive opinion about seasonal influenza vaccine, 39% a neutral opinion, and 22% a negative opinion. Factors associated with a neutral or negative opinion were young age, low educational level, lack of contact with sick or elderly individuals, lack of treatment for a chronic disease and taking a homeopathic preventive treatment. Conclusions: These results show that an important part of the French population does not have a positive opinion about influenza vaccination in France. Furthermore, it allows outlining the profiles of particularly reluctant individuals who could be targeted by informative campaigns.